Why Governments Tax or Subsidize Trade : Evidence from Agriculture - Gawande, Kishore (World Bank, Washington, DC, 2017)
This paper empirically explores the political-economic determinants of why governments choose to tax or subsidize trade in agriculture. The authors use a new data set on nominal rates of assistance (NRA) across a number of commodities spanning the last five decades for 64 countries. NRAs measure the effect on domestic (relative to world) price of the quantitative and price-based instruments used to regulate agricultural markets. The data set admits consideration of both taxes and subsidies on exports and imports. The authors find that both economic and political variables play important roles in determining the within-variation in the NRA data. Based on results the authors offer a number of data-driven exploratory hypotheses that can inform future theoretical and empirical research on why governments choose to tax or subsidize agricultural products an important policy question that is also one of the least understood by scholars.